2022
DOI: 10.3390/jcm11216372
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Prospective Clinical Study for the Evaluation of a Collagen-Hydroxyapatite Composite Scaffold in Hip Revision Surgery

Abstract: One of the greatest challenges of hip revision surgery is the need to restore extensive bone loss by creating a stable reconstruction with long-term durability. The present observational, investigator-initiated prospective study was carried out to evaluate the clinical and radiological results of the use of a commercial biomimetic collagen–hydroxyapatite composite biomaterial (RegenOss) applied in hip revision surgery. Thirty-three patients who underwent hip revision were included in this study, and 29 receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…In agreement with the studies by the authors mentioned above, there is the work of Cimatti P. et al [ 22 ], which takes into consideration the use of these devices in hip revision surgery. The authors of this study performed a 2-year follow-up on 29 patients undergoing revision hip prosthesis surgery, using a collagen–hydroxyapatite composite biomaterial device for the management of bone loss at the acetabular level.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with the studies by the authors mentioned above, there is the work of Cimatti P. et al [ 22 ], which takes into consideration the use of these devices in hip revision surgery. The authors of this study performed a 2-year follow-up on 29 patients undergoing revision hip prosthesis surgery, using a collagen–hydroxyapatite composite biomaterial device for the management of bone loss at the acetabular level.…”
Section: Discussionsupporting
confidence: 85%
“…However, intraoperatively, it is often observed that the original prosthesis remains intact, with complications primarily arising due to inadequate bonding between the prosthesis and surrounding bone tissue. Using new prostheses in revision surgery not only results in the wastage of medical materials but also imposes an economic burden on patients and their families ( Cimatti et al, 2022 ). Currently, there is no definitive research comparing the efficacy of retaining the original prosthesis versus using a new one in revision surgery.…”
Section: Resultsmentioning
confidence: 99%